In situ Product Recovery of Microbially Synthesized Ethyl Acetate from the Exhaust Gas of a Bioreactor by Membrane Technology - Andreas Hoffmann; Alexander Franz; Christian Löser; Thomas Hoyer; Marcus Weyd; Thomas Walther (Engineering in Life Sciences)
ABSTRACT Ethyl acetate is at present exclusively produced from fossil resources. Microbial synthesis of this ester from sugar‐rich waste as an alternative is an aerobic process. Ethyl acetate is highly volatile and therefore stripped with the exhaust gas from the bioreactor which enables in situ product recovery. Previous research on microbial formation of ethyl acetate has focused on the kinetics of ester synthesis and in part on the ester stripping, while the separation of the ester from the exhaust gas has hardly been investigated. A mixed matrix membrane was developed consisting of Silikalite‐1 embedded in polydimethylsiloxane which was installed in a radial–symmetrical membrane module. Evaluation of the separation of ethyl acetate was based on the analysis of the composition of the feed and retentate gas by mass spectrometry. The separation efficiency of the membrane was first tested with varied flows of artificial exhaust gas, containing defined amounts of ethyl acetate. A model for describing the separation process was parametrized by the measured data and used to design a real separation experiment. Ethyl acetate produced from delactosed whey permeate by Kluyveromyces marxianus DSM 5422 in a stirred bioreactor gassed with 0.5 vvm air was successfully separated from the exhaust gas by membranes; 93.6% of the stripped ester was separated. Liquid ethyl acetate was recovered by cooling the permeate gas to ‒78°C, whereby 99.75% of the condensed organic compounds were ethyl acetate. This study demonstrates for the first time that microbially produced and stripped ethyl acetate can be effectively separated from the exhaust gas of bioreactors by membrane technology to obtain the ester in high yield and purity.